x-y=1

Subtract x from both sides of the equation.

-y=1-x

Multiply each term in -y=1-x by -1

Multiply each term in -y=1-x by -1.

(-y)⋅-1=1⋅-1+(-x)⋅-1

Multiply (-y)⋅-1.

Multiply -1 by -1.

1y=1⋅-1+(-x)⋅-1

Multiply y by 1.

y=1⋅-1+(-x)⋅-1

y=1⋅-1+(-x)⋅-1

Simplify each term.

Multiply -1 by 1.

y=-1+(-x)⋅-1

Multiply (-x)⋅-1.

Multiply -1 by -1.

y=-1+1x

Multiply x by 1.

y=-1+x

y=-1+x

y=-1+x

y=-1+x

y=-1+x

Choose any value for x that is in the domain to plug into the equation.

Remove parentheses.

y=-1+0

Add -1 and 0.

y=-1

Use the x and y values to form the ordered pair.

(0,-1)

(0,-1)

Remove parentheses.

y=-1+1

Add -1 and 1.

y=0

Use the x and y values to form the ordered pair.

(1,0)

(1,0)

Remove parentheses.

y=-1+2

Add -1 and 2.

y=1

Use the x and y values to form the ordered pair.

(2,1)

(2,1)

These are three possible solutions to the equation.

(0,-1),(1,0),(2,1)

Find Three Ordered Pair Solutions x-y=1